Feedback Interactions between Trace Metal Nutrients and Phytoplankton in the Ocean - Sunda, William (Frontiers in Microbiology, 2012)
In addition to control by major nutrient elements (nitrogen, phosphorus, and silicon) the productivity and species composition of marine phytoplankton communities are affected by a number of trace metal nutrients (iron, zinc, cobalt, manganese, copper, and cadmium). Of these, iron exerts the greatest limiting influence on carbon fixation rates and has the greatest effect on algal species diversity. It also plays an important role in limiting di-nitrogen (N2) fixation rates, and thus exerts an important influence on ocean inventories of biologically available fixed nitrogen. Because of these effects, iron is thought to play a key role in controlling the biological cycles of carbon and nitrogen in the ocean, including the biological transfer of carbon to the deep sea, the so-called biological CO2 pump, which helps regulate atmospheric CO2 levels and CO2-linked global warming. Other trace metal nutrients (zinc, cobalt, copper, and manganese) have a lesser effect on productivity; but may exert an important influence on the species composition of algal communities because of large differences in metal requirements among algal species. The interactions between trace metals and ocean plankton are reciprocal: not only do the metals affect the plankton, but the plankton regulate the distributions, chemical speciation, and cycling of these metals through cellular uptake and regeneration processes, downward flux of biogenic particles, cellular release of organic chelators, and mediation of redox reactions. This two way interaction has influenced not only the biology and chemistry of the modern ocean, but has had a profound influence on biogeochemistry of the ocean and earth system as a whole, and on the evolution marine and terrestrial biology over geologic history.